Public Debt Tipping Point Studies Ingnore How Exchange Rate Changes May Create A Financial Meltdown - Robin Pope; Reinhard Selten (University of Bonn, Bonn Graduate School of Economics (BGSE), 2011)
In studies concluding that public debt may hamper GDP, the debt tipping effects are estimated as if there were a single world currency. This means that such studies ignore the likely biggest cause of changes in growth rates, namely damage from exchange rate liquidity shocks because we do not live in the fairyland of a single world currency. The conclusions of these studies are accordingly invalid. They deflect attention from a prime danger, namely an exchange-rate-precipitated global meltdown – a danger of the repetition of 80 years ago. These studies are misleading in other respects too. Their estimates of growth determinants conflate the differential growth effects of government expenditures with those of tax concessions and uncollected taxes as contributors to government debt. The conflation entices adherents to see all increases in government debt as arising from excessive expenditures, so that in the current Greek-euro crisis, Greece's real problem, namely tax evasion, is missed, and harmful policies of austerity and depreciation, are proposed that leave the real problem of tax evasion unaddressed. Debt tipping point studies also fail to allow for the increase in wastefulness of private production. This is despite the fact that over the last 40 years, there have been private activities, including key segments of the financial and the pharmaceutical industries, whose expansion has damaged overall health and growth. The upshot is misdirected policy analysis and advice. Policy should instead be directed to adequate employment-generating fiscal stimulus in a global downturn, to extracting from the well-to-do adequate taxes, to averting further damage from exchange rate liquidity shock by creating a single world money, and to ensuring that for profit activities in the pharmaceutical and financial industries are adequately regulated, and where this is infeasible, shut down and replaced with fiscally stimulated productive activities.
Keywords: E6; F31; G01; H62; I18; 330; Hitler; exchange rates; employment multipliers; private sector inefficiency; central bank cooperation; central bank conflict; public debt; tipping points; uncertainty; financial sector; pharmaceutical sector; World War 2; Korean War; fiscal stimulus